2015
DOI: 10.1136/bmjquality.u209049.w3670
|View full text |Cite
|
Sign up to set email alerts
|

Hypokalaemia: Improving the investigation, management and therapeutic monitoring of hypokalaemic medical inpatients at a district general hospital

Abstract: Hypokalaemia is prevalent in 20% of hospitalised patients. Furthermore, inadequate management of hypokalemia was identified in 24% of these patients. Associated with significant patient morbidity and mortality, the identification, investigation, and treatment of hypokalaemia was identified as an area for improvement in the management of medical inpatients.The project aims to measure the assessment, management, and therapeutic monitoring of medical inpatients with hypokalaemia in a district general hospital.All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…One similar project is reported in the BMJ Quality Improvement Reports journal in which there was an uncertainty of appropriate investigation and management of hypokalaemia including lack of medication review, ECG assessments, and blood monitoring leading to hyperkalaemia 8. This was not an issue in our study however the interventions made and improvement outcomes were similar.…”
Section: Introductionsupporting
confidence: 63%
“…One similar project is reported in the BMJ Quality Improvement Reports journal in which there was an uncertainty of appropriate investigation and management of hypokalaemia including lack of medication review, ECG assessments, and blood monitoring leading to hyperkalaemia 8. This was not an issue in our study however the interventions made and improvement outcomes were similar.…”
Section: Introductionsupporting
confidence: 63%
“…Previous investigations, including our published study, have shown that hypokalemia is associated with unfavorable outcomes including increased mortality and prolonged hospital stay for TBI patients 3,5 . Yet, clinical signs of hypokalemia are often confounded with injuries and underlying diseases during the acute phase of TBI, which may lead to delayed diagnosis and unfavorable consequences 6 . It is therefore hypothesized that identifying patients with high risks of hypokalemia at the earliest stage may provide chances of prophylactic treatment and improve outcomes for TBI patients.…”
Section: Introductionmentioning
confidence: 78%
“…Total-body potassium is predominantly present as an intracellular component. In clinical medicine, hypokalemia is one of the most frequently electrolyte abnormalities, affects multiple organ systems, and contributes to a significant risk of morbidity and mortality ( Crop et al, 2007 ; Jordan & Caesar, 2015 ).…”
Section: Discussionmentioning
confidence: 99%